Does Using Word Wall Website Improve Students’ Vocabulary Retrieving? - agustia; Ahmad Munawir; Ridwan (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
This research aims to know the significant influence between the use of word wall website improve students’ vocabulary mastery. This research is done by using quantitative method with quasi experimental design. In this research, the researchers used random sampling as the technique. The researchers choose second grade students at SMPN 2 Majene as the samples of the research. From the data analysis computed by using SPSS, it was obtained from Mann-Whitney Test that Sig. (2-tailed) at 0.000<0.05, then as the basis for decision that h0 is rejected and h1 is accepted. Based on the result of the research that has been done by the writers, the researchers concluded that using word wall website has a significant effect in improving students’ vocabulary mastery.